Enhancement Of Volatile Fatty Acid Production From Anaerobic Treatment Of Palm Oil Mill Effluent - Lim, Jing Xiang (2019)
Biological treatment unit is widely used to treat high organic content wastewater such as palm oil mill effluent (POME). A treatment that can salvage the useful nutrient from the wastewater is needed to enhance the sustainability of the wastewater treatment process. Volatile fatty acid (VFA) has high potential to be applied on many application such as production of biogas or biodegradable plastic. The recovery of nutrient in the form of methane gas (end-product of anaerobic digestion) was well researched but the study on the enhancement of volatile fatty acid (VFA) (intermediate-product of anaerobic digestion) was still limited. VFA production is preferred over biogas production because VFA can be used to produce more valuable product such as polyhydroxyalkanoate (PHA) (a type of biodegradable plastic). The enhancement of VFA production was achieved through the elimination of methanogenesis process. In this study, a sequencing batch reactor was used to enrich the biomass in partial anaerobic treatment of POME to enhance the VFA production. The SBR has a working volume of 8 L and hydraulic retention time of 5 days. The influent concentration of POME contains about 33400 mgCOD/L. The anaerobic reactor managed to increase the VFA accumulation to about 10500 mg/L total VFA (about 43.8 % of VFA accumulation in the feed). The microbial population analysis had revealed that the growth of methanogen was suppressed and no methane gas was release during the treatment process. Further, it was discovered that the increase of ammoniacal nitrogen has increased the total VFA production. About 105.7 % VFA accumulation was achieved at COD:N ratio of about 40:5. However, inhibition on the VFA production occurred at ammoniacal nitrogen content of more than 4000 mg/L shock loading. Furthermore, the effluent from the VFA enhancement reactor was used as the feed to produce PHA. The aerobic reactor accumulating PHA using VFA enriched POME (AE1) has achieved output PHA concentration of about 3773 mgPHA/L (specific production of about 0.32 mgPHA/mgVSS). The results shows that the recovery of the VFA has high potential to produce biodegradable plastic (PHA). Additionally, the microbial growth kinetics was evaluated for the microorganism in VFA enhancement reactor and PHA production reactor. The result of the growth kinetics studies was used to simulate the VFA accumulation and the PHA production by using MATLAB software.